Gender-Equality Concerns and Political Attitudes toward Women in the 2019 Legislative Election: Evidence from Pelalawan - Andhik Beni Saputra; Azhari Setiawan; Citra Puspita Febriani (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
The presence of women in Indonesian politics remains underrepresented whereas cultural and societal aspects pose critical influence in determining voter behavior toward female candidates. The aim of this article is to examine voter behavior regarding female candidates and the probability for them to be elected as members of parliament. We apply quantitative method by developing three models representing three combinations of predictor variables, (i) socio-demography, (ii) gender- equality concern, and (iii) political attitude towards female candidates as determinants towards female candidate electability. The study took place in Pelalawan Regency in Riau Province, by analyzing 400 respondents with equal numbers of men and women from various socio-economic backgrounds through clustered random sampling method. We tested these hypotheses and our three models by utilizing logistic regression analysis. The result shows that political attitude toward female candidates (Model 3) are the strongest coefficient and most significant determinant for female candidate electability. The study also revealed that female candidate’s electability in Pelalawan Regency is lower than male candidate’s electability among male respondents. On the other hand, female candidate’s electability is higher than male candidate’s electability among female respondents. Moreover, we also found that education determines female candidate’s electability where the more educated an individual is, the more he/she tends to vote for female candidates.